TINJAUAN KRITIK SOSIAL TERHADAP LAGU BENTO KARYA IWAN FALS BERTAFSIR POLITIK - Mufahanim Ananda Putri; Taufik Nur Hidayah; Titik Sudiatmi (Jurnal Bastra (Bahasa dan Sastra), 2024)
Reflects the overall substance of the article's content and allows  Music is part of works of art that functions as a fairly effective means of mass communication to the public. This research aims to analyze and interpret the political elements in the song Bento by Iwan Fals. Through a political literary criticism approach, this article examines how Iwan Fals uses his lyrics to the song Bento as a medium to voice criticism of government policies, social injustice and other political issues. The method used is text analysis with a qualitative approach, where several lyrics in the song Bento by Iwan Fals which are considered to have political content are analyzed in depth.